2020
DOI: 10.1016/s2666-7568(20)30004-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective interventions for potentially modifiable risk factors for late-onset dementia: a costs and cost-effectiveness modelling study

Abstract: Background The potential economic value of interventions to prevent late-onset dementia is unknown. We modelled this for potentially modifiable risk factors for dementia.Methods For this modelling study, we searched PubMed and Web of Science from inception to March 12, 2020, and included interventions that: successfully targeted any of nine prespecified potentially modifiable risk factors (hypertension, diabetes, hearing loss, obesity, physical inactivity, social isolation, depression, cigarette smoking, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…24 This might be a relatively simple but cost-effective intervention for New Zealand that may result in the more equitable reduction of dementia risk across all major ethnic groups living in New Zealand. Indeed, a recent cost modelling study in the UK 47 demonstrated not only a reduction in dementia prevalence and quality adjusted life year gains for the individual associated with the provision of hearing aids but also a net cost saving to the care system.…”
Section: Discussionmentioning
confidence: 99%
“…24 This might be a relatively simple but cost-effective intervention for New Zealand that may result in the more equitable reduction of dementia risk across all major ethnic groups living in New Zealand. Indeed, a recent cost modelling study in the UK 47 demonstrated not only a reduction in dementia prevalence and quality adjusted life year gains for the individual associated with the provision of hearing aids but also a net cost saving to the care system.…”
Section: Discussionmentioning
confidence: 99%
“…The Article by Naaheed Mukadam and colleagues 8 in this issue of The Lancet Healthy Longevity must be seen in light of this situation. This paper is a valuable contribution to the scarce literature of the health economics of dementia prevention.…”
Section: The Art Of Simulationmentioning
confidence: 99%
“…There are different ways to integrate modification of several risk factors to reflect their adjusted effect. The use of weighted population-attributable fractions (used in Mukadem and colleagues' Article 8 ) is one interesting approach. Another approach is to use a multivariate risk model such as the CAIDE index, 9 which was used in the FINGER project.…”
Section: The Art Of Simulationmentioning
confidence: 99%
“…As shown in a very recent UK study, effective intentions for potentially modifiable risk factors of dementia would save £1863 billion annually in England, reduce dementia prevalence by 8.5% and produce gains in quality-adjusted life year. 7 In societies where the proportions of undiagnosed dementia are particularly high, risk-predictive algorithms may even serve as a valuable tool to support early diagnosis of dementia.…”
Section: Introductionmentioning
confidence: 99%